Reinventing Government Dinas Kebudayaan dan Pariwisata Bojonegoro dalam Pengembangan Pariwisata - Desy Alya Putri Rahmasari; Taufiq, Achmad; Junadi (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to find out how reinventing government in tourism development as an increase in local revenue. Reinventing Government is a government effort to change the type of services to be provided to the public with implementing a new system by transforming the public sector into entrepreneurship. The methode used in this research is a qualitative method with a descriptive approach. Data collection techniques through interview, observation, and documentation. The focus of this research is how the tourism development effort of the Bojonegoro Regency Culture and Tourism office in the concept of reinventing government. The results of this study indicate that the Bojonegoro Regency Culture and Tourism office has implemented 9 of the 10 principles of reinventing government. The principle that has not been implemented is the principle of anticipatory government which is caused by involving many parties so that it requires a long procces. Even though it has implemented 9 of the 10 principles of reinventing government, it does not guarantee that the Disbudpar bojonegoro is able to achieve PAD target beacause there is still a lack of maximum implementation of each principle that has been implemented by the Regency Culture and Tourism office so that it has not been able to achive the predetermined local revenue target.